Informationsrepertoires von Menschen mit Beeinträchtigungen Barrieren und Förderfaktoren für die gleichberechtigte Teilhabe an öffentlicher Kommunikation - Haage, Anne (Lebensweltbezogene Medienforschung: Angebote - Rezeption - Sozialisation, 2021)
This study examines the participation of people with disabilities in public communication from a user's perspective. To this end, research instruments from two disciplines were combined: the ICF classification system from inclusion research and the scope of information approach from media studies. On the one hand, this approach enables the author to measure the diversity of media use in a user-centred way and, on the other hand, to include the entire range of context factors in the search for barriers to and facilitators of participation in public communication, not just barriers in the media. With the help of a cluster analysis of typical ranges of information, the author is able to identify constellations that particularly enable or disable such participation.